Approximation of functions from the class C^ψ_β, ∞ by Poisson biharmonic operators in the uniform metric - Zhyhallo, T. V.; Kharkevych, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We obtain asymptotic equalities for upper bounds of approximations of functions from the class C^ψ_β, ∞ by the Poisson biharmonic operators in the uniform metric.